Multimorbidity prevalence and pattern in Indonesian adults: an exploratory study using national survey data - Hussain, M.; Huxley, Rachel; Al Mamun, A. (2015)
OBJECTIVES: To estimate the prevalence and pattern of multimorbidity in the Indonesian adult population. DESIGN: Cross-sectional study. SETTING: Community-based survey. The sampling frame was based on households in 13 of the 27 Indonesian provinces, representing about 83% of the Indonesian population. PARTICIPANTS: 9438 Indonesian adults aged 40 years and above. MAIN OUTCOME MEASURES: Prevalence and pattern of multimorbidity by age, gender and socioeconomic status. RESULTS: The mean number of morbidities in the sample was 1.27 (SE±0.01). The overall age and sex standardised prevalence of multimorbidity was 35.7% (34.8% to 36.7%), with women having significantly higher prevalence of multimorbidity than men (41.5% vs 29.5%; p<0.001). Of those with multimorbidity, 64.6% (62.8% to 66.3%) were aged less than 60 years. Prevalence of multimorbidity was positively associated with age (p for trend <0.001) and affluence (p for trend <0.001) and significantly greater in women at all ages compared with men. For each 5-year increment in age there was an approximate 20% greater risk of multimorbidity in both sexes (18% in women 95% CI 1.14 to 1.22 and 22% in men 95% CI 1.18 to 1.26). Increasing age, female gender, non-Javanese ethnicity, and high per-capital expenditure were all significantly associated with higher odds of multimorbidity. The combination of hypertension with cardiac diseases, hypercholesterolemia, arthritis, and uric acid/gout were the most commonly occurring disease pairs in both sexes. CONCLUSIONS: More than one-third of the Indonesian adult population are living with multimorbidity with women and the more wealthy being particularly affected. Of especial concern was the high prevalence of multimorbidity among younger individuals. Hypertension was the most frequently occurring condition common to most individuals with multimorbidity.